2017
DOI: 10.1016/j.enbuild.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis applied to performance of buildings in Europe

Abstract: Energy performance of buildings generally assesses the energy consumption of buildings such as heating, domestic heat water, ventilation systems, etc. However, this approach is based on the first law of thermodynamics and considers only the quantity of energy used without considering its 'quality' and leads to a lack of information about the energy conversion processes. This is particularly true in the new low-energy buildings where sometimes high temperatures sources are used to meet low-temperature needs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Energy consumption by building sector approach takes into account only the quantity of energy used in buildings, without actual quality of the used energy, which is further possible to achieve using also exergy analysis [6]. Sartor and Dewallef [6] studied four selected buildings, using energy performance building software, and compared both specific energy and exergy use. Their results showed that the best system from the energy and exergy perspective is domestic heat network connection followed with heat pumps.…”
Section: • 49 Th International Hvacandr Congress and Exhibitionmentioning
confidence: 99%
“…Energy consumption by building sector approach takes into account only the quantity of energy used in buildings, without actual quality of the used energy, which is further possible to achieve using also exergy analysis [6]. Sartor and Dewallef [6] studied four selected buildings, using energy performance building software, and compared both specific energy and exergy use. Their results showed that the best system from the energy and exergy perspective is domestic heat network connection followed with heat pumps.…”
Section: • 49 Th International Hvacandr Congress and Exhibitionmentioning
confidence: 99%
“…However, according to the First Law of Thermodynamics, energy is rather a conservative magnitude and, as such, it is neither possible to destroy it nor create it, instead it is only possible to transform it from one form into another [2]. On the other hand, the Second Law of Thermodynamics states that although energy cannot be created or destroyed, its quality may be actually degraded [3]. Thus, in order to perform a thorough energy analysis, it is also necessary to bear in mind the statement of the Second Law of Thermodynamics, from which the concept of exergy springs.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of energy and exergy parameters of the GWHP system is the subject of many papers. Sartor and Dewallef [4] compared the energy and exergy needs of different heating systems on the example of four different types of buildings. Their results showed that the best heating system is a heat pump connected to the domestic heat network.…”
Section: Introductionmentioning
confidence: 99%